Chaotic Honeybees Optimization Algorithms Approach for Traveling Salesperson Problem. (11th October 2022) - Palominos, Pedro; Ortega, Carla; Alfaro, Miguel; Fuertes, Guillermo; Vargas, Manuel; Camargo, Mauricio; Parada, Victor; Gatica, Gustavo
Abstract : Due to the difficulty in solving combinatorial optimization problems, it is necessary to improve the performance of the algorithms by improving techniques to deal with complex optimizations. This research addresses the metaheuristics of marriage in honey-bees optimization (MBO) based on the behavior of bees. The current study proposes a technique for solving combinatorial optimization problems within proper computation times. The purpose of this study focuses on the travelling salesperson problem and the application of chaotic methods in important sections of the MBO metaheuristic. Three experiments were conducted to measure the efficiency and quality of the solutions: (1) MBO with chaos to generate initial solutions (MBO2); (2) MBO with chaos in the workers (MBO3); and (3) MBO with chaos to generate initial solutions and the workers (MBO4). The application of chaotic functions in MBO was significantly better at solving the travelling salesperson problem.